Pharmacogenetics of myotonic hNav1.4 sodium channel variants situated near the fast inactivation gate. (March 2019) - Farinato, Alessandro; Altamura, Concetta; Imbrici, Paola; Maggi, Lorenzo; Bernasconi, Pia; Mantegazza, Renato; Pasquali, Livia; Siciliano, Gabriele; Lo Monaco, Mauro; Vial, Christophe; Sternberg, Damien; Carratù, Maria Rosaria; et al.
Graphical abstract: Abstract: Sodium channel myotonia and paramyotonia congenita are caused by gain-of-function mutations in the skeletal muscle voltage-gated sodium channel hNav1.4. The first-line drug is the sodium channel blocker mexiletine; however, some patients show side effects or limited responses. We previously showed that two hNav1.4 mutations, p.G1306E and p.P1158L, reduce mexiletine potency in vitro, whereas another sodium channel blocker, flecainide, is less sensitive to mutation-induced gating defects. This observation was successfully translated to p.G1306E and p.P1158L carriers. Thus, the aim of this study was to perform a pharmacological characterization of myotonic Nav1.4 mutations clustered near the fast inactivation gate of the channel. We chose seven mutations (p.V1293I, p.N1297S, p.N1297K, p.F1298C, p.G1306E, p.I1310N, and p.T1313M) from the database of Italian and French networks for muscle channelopathies. Recombinant hNav1.4 mutants were expressed in HEK293T cells for functional and pharmacological characterization using the patch-clamp technique. All the studied mutations impair the kinetics and/or voltage dependence of fast inactivation, which is likely the main mechanism responsible for myotonia. The severity of myotonia is well-correlated to the enhancement of window currents generated by the intersection of the activation and fast inactivation voltage dependence. Five of the six mutants displaying a significant positive shift of fast inactivation voltage dependence reduced mexiletine inhibition in an experimental condition mimicking myotonia. In contrast, none of the mutations impairs flecainide block nor does p.T1313M impair propafenone block, indicating that class Ic antiarrhythmics may constitute a valuable alternative. Our study suggests that mutation-driven therapy would be beneficial to myotonic patients, greatly improving their quality of life.